Erratum: MEL C. CAMELO & MARCUS A.N. COELHO (2024) A new species of Anthurium (Araceae) from the canga vegetation of the Serra dos Carajás, Pará, Brazil. Phytotaxa 652 (2): 142–148. - Camelo, Mel C.; Coelho, Marcus A.n. (Phytotaxa, 2024)
N/A